PENGARUH PENERAPAN METODE BERCERITA DENGAN GAMBAR SERI TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 4-5 TAHUN DI PENDIDIKAN ANAK USIA DINI AISYIYAH 1 KECAMATAN SENAPELAN PEKANBARU - Betrisa Afrina; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study is based on observations in the field of the listening skills of children aged 4-5 years are still low. So it is necessary to use storytelling to improve the listening skills. This study aims to determine the effect of storytelling method with the image series for children in early childhood listening skills Aisyiyah 1. The subjects used in this study is 15 people. The data collection techniques were used that observation. Data were analyzed using t-test using SPSS 17.0. The research hypothesis is that there is a very significant influence on the ability to listen to children aged 4-5 years in early childhood Aisyiyah 1 after applying storytelling with the picture series. It can be seen from the data analysis showed an average difference of -3,410a and sig (2 tailed) of 0.001. That is sig <0.05 so ha ho accepted and rejected. It can be concluded that there are differences listening skills of children aged 4-5 years are very significant after using storytelling with images of the series to 4-5 years of age listening skills in early childhood Aisyiyah 1 Senapelan District Pekanbaru.Keywords: Ability Listening, Method Of Storytelling With Pictures Series